COLAR: open-label clinical study of IL-6 blockade with tocilizumab for the treatment of immune checkpoint inhibitor-induced colitis and arthritis. Issue 9 (12th September 2022) - Holmstroem, Rikke Boedker; Nielsen, Ole Haagen; Jacobsen, Søren; Riis, Lene Buhl; Theile, Susann; Bjerrum, Jacob Tveiten; Vilmann, Peter; Johansen, Julia Sidenius; Boisen, Mogens Karsbøl; Eefsen, Rikke Helene Løvendahl; Marie Svane, Inge; Nielsen, Dorte Lisbet; et al.
Abstract : Background: Immune-related adverse events due to immune checkpoint inhibitors (ICIs) are not always effectively treated using glucocorticoids and it may negatively affect the antitumor efficacy of ICIs. Interventional studies of alternatives to glucocorticoids are lacking. We examined whether interleukin-6 blockade by tocilizumab reduced ICI-induced colitis and arthritis. Patients and methods: Patients with solid cancer experiencing Common Terminology Criteria for Adverse Events (CTCAE v5.0) grade >1 ICI-induced colitis/diarrhea (n=9), arthritis (n=9), or both (n=2) were recruited and treated with tocilizumab (8 mg/kg) every 4 weeks until worsening or unacceptable toxicity. Patients were not allowed to receive systemic glucocorticoids and other immunosuppressive drugs within the 14-day screening period. The primary endpoint was clinical improvement of colitis and arthritis, defined as ≥1 grade CTCAE reduction within 8 weeks. Secondary endpoints were improvements and glucocorticoid-free remission at week 24; safety; radiologic, endoscopic, and histological changes; and changes in plasma concentrations of C reactive protein, cytokines (IL-6, IL-8, and IL-17), and YKL-40. Results: Nineteen patients were available for efficacy analysis; one patient was excluded due to pancreatic insufficiency-induced diarrhea. Patients received treatment with pembrolizumab (n=10) or nivolumab (n=4) as monotherapy or ipilimumab and nivolumab (n=5) combined. Seven patients had been initially treated with glucocorticoids, and two of them also received infliximab. Ten patients continued ICI therapy during tocilizumab treatment. The primary endpoint was achieved in 15 of 19 (79%) patients. Additional one patient had ≥1 grade reduction at week 10, and another patient had stabilized symptoms. At week 24, ongoing improvement without glucocorticoids (n=12), including complete remission (n=10), was noted. Five patients had grades 3–4 treatment-related adverse events, which were manageable and reversible. Conclusions: Tocilizumab showed promising clinical efficacy and a manageable safety profile in the treatment of ICI-induced colitis and arthritis. Our findings support the feasibility of randomized trials of immune-related adverse events. Trial registration number: NCT03601611 .